The Benefit of Continuous Hydrological Modelling for Drought Hazard Assessment in Small and Coastal Ungauged Basins: A Case Study in Southern Italy - De Luca, Davide Luciano; Apollonio, Ciro; Petroselli, Andrea (Climate (Basel), 2022)
Rainfall-runoff modelling in small and ungauged basins represents one of the most common practices in hydrology. However, it remains a challenging task for researchers and practitioners, in particular in a climate change context and in areas subject to drought risk. When discharge observations are not available, empirical or event-based approaches are commonly used. However, these schemes can be affected by several relevant assumptions. In the last years, continuous models have been developed in order to address the major drawbacks of event-based approaches. With this goal in mind, in this work we applied a synthetic rainfall generation model (STORAGE; stochastic rainfall generator), constituting the implementation of a modified version of Neymann-Scott rectangular pulse (NSRP) model, and a continuous rainfall-runoff framework (COSMO4SUB; continuous simulation modelling for small and ungauged basins) specifically designed for ungauged basins within a climate change context. The modeling approach allows one to investigate the drought hazard using specific indicators for rainfall and runoff in a small watershed located in southern Italy. Results show that the investigated area seems to tend to a mild/moderate drought in a future time period of approximately 30 years, with a decrease in seasonal water volumes availability in the range of 15–30%. Finally, our results confirm that the continuous modelling is suitable for rapid and effective design simulations supporting drought hazard assessment.